Pengaruh Literasi Keuangan dan Persepsi Risiko pada Mahasiswa di Surabaya Terhadap Pencegahan Investasi Ilegal - Nadya Meisya Nilasetiyowati; Yanthi, Merlyana Dwinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Students utilize technology to invest which can make it easier for them to access and learn about financial understanding. However, if access to investment is not balanced with an understanding of investment products and their mechanisms in the hope of getting large returns, it will become an opportunity for perpetrators of investment fraud. The aim of this research is to determine the influence of financial literacy and risk perception among students in Surabaya on preventing illegal investment. The method used in this research is quantitative. The population in this study were students who invested and were registered in 14 university investment galleries in Surabaya so that the sample obtained was 100 respondents and used a purposive sampling technique. Data collection is by using a questionnaire with Google Form. The results of the research show that financial literacy influences the prevention of illegal investment, risk perception influences the prevention of illegal investment and financial literacy and risk perception simultaneously influence the prevention of illegal investment.